One Thousand Working Papers - Carlo Carraro; Alessandro Lanza; Valeria Papponetti (Fondazione Eni Enrico Mattei (FEEM), 2003)
At the end of 2002, FEEM celebrated a major achievement in its publication history: 1000 published working papers. This paper provides an analysis of FEEM working papers according to different viewpoints. First, it assesses the evolution of the contents of FEEM working papers by identifying the main research areas that they cover and how these research areas have evolved over time. Then, it quantifies the success of FEEM working papers by computing the number of downloads from FEEM web site and the quantity and quality of subsequent publications in top economic journals. Finally, it compares the number of working papers published by FEEM with those published by other leading research institutions both in Europe and the US.
Keywords: 330; Bibliometrie